Biosíntesis de dextrano por Leuconostoc mesenteroides y su aplicación como floculante para el tratamiento de efluentes de la industria azucarera - De La Cruz Noriega, Magaly (2019)
ABSTRACT The present investigation has as purpose production of biofloculant dextran using Leuconostoc mesenteroides var mesenteroides isolated from residual cane juice, as well as, to evaluate its in vitro flocculant activity in effluents from la azucarera Cartavio S.A.A. Leuconostoc mesenteroides var mesenteroides was isolated from 15 samples of residual cane juice from the fields of Casa Grande S.A.A. for which 0.1 ml of juice of the dilution of 105 was inoculated in MSE agar selective medium (Mayeux, Sandine & Elliker) and incubated at 30 ° C for 48 hours, at pH 7.2. The bacteria were isolated by obtaining four biochemically identified strains according to the Bergey’s Manual of Bacteriological Determination. The strain encoded as LM03 was identified as L mesenteroides var mesenteroides producing the best dextran production results with minimum values of 2.61 g / L and maximum of 26.87 g / L at times of 4 and 80 hours respectively, resulting in being pure dextran according to FT-IR analysis. To evaluate the flocculant activity of dextran, a pitcher test equipment Phipps & Bird, USA, and turbidity was used with a Termo Scientific brand nephelometer. The samples were obtained from the effluent of the Azucarera Cartavio S.A.A., adjusted to pH 7, 8, 9, 10 and 11 for a constant dose of 40 ppm dextran, fast and slow speed 150 and 50 rpm, respectively. To evaluate the best dose, values of 5, 20 and 40 ppm of dextran were used with fast stirring speeds of 180 and 150 and slow speeds of 30 and 50, respectively. The best conditions obtained were at the dose of 40 ppm dextran with rapid stirring speed of 150 rpm for 5 min; slow speed of 50 rpm for 15 min and at pH 9, which resulted in a 77.7% removal of the turbidity of the problem water. It was concluded that, the isolated strain was L. mesenteroides var. mesenteroids, with a dextran production of 26.87 g / L at 80 hours and with a dose of 40 ppm and at pH 9, dextran has a greater flocculant effect.